Temperate and boreal rainforests of the world ecology and conservation - DellaSala, Dominick A.; SpringerLink (Online service). (Washington, DC Island Press, 2011)
In the first book of Its Kind, DellaSala brings together leading scientists from around the world to describe the ecology and conservation of temperate and boreal rainforests, unique ecosystems that are largely overlooked but rich in plants and wildlife and containing some of the most massive trees on Earth. Temperate and Boreal Rainforests of the World offers a global vision rooted in ecological science for all who are concerned about the plight of these remarkable forests.
Foreword; D. Suzuki - Preface; D.A. DellaSala - 1. Just What Are Temperate and Boreal Rainforests?; D.A. DellaSala et al - 2. Temperate and Boreal Rainforests of the Pacific Coast of North America; D.A. DellaSala et al - 3. Temperate and Boreal Rainforests of Inland Northwestern North America; D.A. DellaSala et al - 4. Perhumid Boreal and Hemiboreal Forests of Eastern Canada; S.R. Clayden et al - 5. ValdivianTemperate Rainforests of Chile and Argentina; D. Tecklin et al - 6. Temperate and Boreal Rainforest Relicts of Europe; D.A. DellaSala et al - 7. Temperate Rainforests of Japan; Y. Nakamura et al - 8. Temperate Rainforests of Australasia; J.B. Kirkpatrick, D.A. DellaSala - 9. Rainforests at the Margins:Regional Profiles; D.A. DellaSala. Regional Profile: Colchic and HyrcanicTemperate Rainforests of the Western Eurasian Caucasus; G. Nakhutsrishvili et al. Regional Profile: Humidity-Dependent Forests of the Russian Far East, Inland Southern Siberia, and the Eastern Korean Peninsula; P.V. Krestov et al. Regional Profile: Knysna-TsitsikammaTemperate Rainforests of South Africa; P.E. Hosten, J.M. Rossa - 10. Crosscutting Issues and Conservation Strategies; D. A. DellaSala et al - 11. A Global Strategy for Rainforests in the Era of Climate Change; J. Fitzgerald et al - Contributors - Index.
Electronic reproduction.
Keywords: Rain forest ecology; Taiga ecology; Temperate climate; Rain forest conservation; Taiga conservation; Electronic books